A brand specific investigation of international cost shock threats on price and margin with a manufacturer-wholesaler-retailer model - Till Dannewald; Lutz Hildebrandt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
In times of increasing oil prices and a weak dollar, European companies that focus their business on the US market may find themselves in a weak position. While many businesses can hedge this kind of risk by relocating production to the US, or employing financial remedies, these strategies may not work throughout the consumer goods industry. Especially for brands whose consumption is strongly impacted by country of origin (e.g. French whine, Swiss chocolate, German beer, etc.), there are only limited possibilities to bypass these challenges. To react efficiently to these threats, managers need a precise picture of complete market mechanisms before they can set up an appropriate marketing strategy to react. We aim to enhance the understanding of market mechanisms that are caused by exogenous cost shocks for typical consumer goods. The contribution of our work is twofold: To investigate the underlying process and to derive concrete managerial suggestions. We hereby propose a combination of two different empirical frameworks to measure the effects of exchange rate variations in fast moving consumer markets. Furthermore we extend existing work in being the first to model vertical interactions with a Manufacturer-Wholesaler-Retailer Model. Within this framework we investigate how changes in local currency affect the strategic management variables of price, margin and profit in a typical consumer goods market. While it is widely known that exchange rate changes cause variations in export/import prices and numerous studies show that the effect of currency fluctuations decreases within the distribution process, recent marketing research in this area has not explicitly accounted for the mechanisms that occur within the distribution channel. Many empirical studies implicate that exogenous cost shocks, which are caused by exchange rate changes, are passed through imperfectly to final consumer prices. We therefore show that the margins of the players involved in the distribution process will be affected differently by exchange rate variation dependent on the competitive situation. Although our empirical study focuses on the effect of exchange rate variations on strategic marketing variables of a selected fast moving consumer good, our framework can be easily adapted to any other market and other sources that cause a change in production cost.
Keywords: M31; F12; L66; F14; L13; 330; Exchange rate pass-through; structural choice modelling; endogeneity; international marketing; pricing; channel management; Internationales Marketing; Konsumgüterindustrie; Lieferanten-Kunden-Beziehung; Exchange Rate Pass-Through; Kosten; Schock; Betriebliche Preispolitik; Vertriebsweg; Theorie; Schätzung; Bier; Export; Europa; Import; USA